A socio-ecological landscape analysis of human–wildlife conflict in northern Botswana. Issue 5 (2nd September 2020) - Dunnink, Jeffrey A.; Hartley, Robyn; Rutina, Lucas; Alves, Joana; Franco, Aldina M. A.
Abstract: Human–wildlife conflict is one of the most pressing issues in conservation. Low-income rural communities are disproportionately affected by negative interactions with large predators, which often leads to retaliatory killings and persecution of the animals. To overcome this, socio-ecological studies that merge existing knowledge of large predator ecology with long-term livestock depredation monitoring are required. We examined patterns and drivers of livestock depredation in northern Botswana, using a mixed effects model of the government's long-term monitoring data on human–wildlife conflict, to identify ways to reduce depredation at key spatial and temporal scales. We compared the results to farmers' understanding of their personal risk within the landscape. We analysed 342 depredation events that occurred during 2008–2016, using variables measured at different scales. The variables affecting the locations of depredation events at the 2-km scale were distance to protected areas and predator and herbivore density, with increased depredation in the wet season. At a 1-km scale, herbivore density did not have a significant effect, but the effect of other variables was unchanged. The 4-km scale model was influenced by livestock and herbivore density, with increased depredation in the wet season. Livestock depredation could be reduced by establishing an 8-km livestock-free buffer along the protected area boundary. There was disparity between government data on human–wildlife conflict, depredation reported by farmers in interviews and farmers' risk awareness. Farmers would benefit from workshops providing tools to make evidence-based decisions and minimize their risk of negative interactions with wildlife. This would ultimately contribute to wildlife conservation in the Kavango-Zambezi Transfrontier Conservation Area.